Quality of service as a driver of brand awareness in the aviation industry: A systematic review of the literature - Astri Rumondang Banjarnahor; Juliater Simarmata; Imam Ozali; Binsar Renold Sitorus; Sven Buyle (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2025)
This study analyzes the relationship between service quality, brand image, and brand awareness in the aviation industry. Using the Systematic Literature Review (SLR) approach following PRISMA guidelines, this study identifies major trends and gaps in related literature. The results show that superior service quality is important in forming a strong brand image and increasing brand awareness. Further analysis reveals that service quality dimensions such as reliability, convenience, and responsiveness greatly contribute to the positive perception of the brand image. In addition, a strong brand image also increases consumer loyalty and repeat purchase intent through a positive word-of-mouth mechanism. This research emphasizes the importance of a customer-focused service strategy to strengthen the airline's competitive position in an increasingly complex and dynamic global market. This study's theoretical and practical implications guide airlines in formulating holistic and responsive strategies to market dynamics.